2019
DOI: 10.1177/1534735419827098
|View full text |Cite
|
Sign up to set email alerts
|

Network Meta-Analysis of Chinese Herbal Injections Plus the FOLFOX Regimen for the Treatment of Colorectal Cancer in China

Abstract: The aim of the present network meta-analysis (NMA) was to explore the comparative effectiveness and safety of different Chinese herbal injections (CHIs) combined with the FOLFOX regimen versus FOLFOX alone for colorectal cancer (CRC). Methods: A comprehensive search for randomized controlled trials (RCTs) was performed with regard to different CHIs for treating CRC in several electronic databases up to July 2016. The quality assessment of the included RCTs was conducted according to the Cochrane risk of bias t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…[ 20 , 22 , 34 ] In recent years, KLT injection has been widely used in the treatment of colorectal cancer, with significant efficacy. [ 35 ] Yet the evidence from the RCTs is inconsistent. With the increasing number of clinical trials, it is urgent to systematically evaluate the efficacy of KLT injection in the treatment of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 , 22 , 34 ] In recent years, KLT injection has been widely used in the treatment of colorectal cancer, with significant efficacy. [ 35 ] Yet the evidence from the RCTs is inconsistent. With the increasing number of clinical trials, it is urgent to systematically evaluate the efficacy of KLT injection in the treatment of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…and irinotecan, which are combined in clinical practice [2], but treatment is difficult if resistance occurs [18]. Traditional Chinese medicine is expected to be an ideal agent for reversing MDR after the failure of chemotherapy for tumours due to its low toxicity, good stability, and unique effects [8,9,19]. In fact, identification of a Chinese medicine preparation that is sensitive, reduces toxicity, shows synergistic and complementary effects with drugs, and reduces drug resistance is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies to date have shown the potential for the development of traditional Chinese medicine to treat tumour MDR. Compound radix Sophorae injection is a traditional Chinese medicine that exerts antioxidant effects, protects the liver, enhances immunity, and provides chemotherapeutic sensitivity [9][10][11]. e injection is prepared from extracts of radix Sophora flavescens, poriacocoscocos, and pachycocoscocos, and the main effective components are oxymatrine, sophorine, and matrine.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, this study included 8 DSCIs, namely, Danshen injection (DS), Fufang Danshen injection (FFDS), Danhong injection (DH), Dansenduofensuanyan injection (DSDFSY), Danshen Salvianolic Acids injection (DSSA), Danshenchuanxiongqin injection (DSCXQ), Sodium Tanshinone IIA Sulfonate injection (STS) and Guanxinning injection (GXN). Compared with the traditional double-arm meta-analysis, network meta-analysis (NMA) can synthesize different interventions for the same disease and perform direct or indirect comparisons ( Grant, 2019 ; Sun et al, 2019 ; Zhang et al, 2019 ). Moreover, NMA can assist assessing and ranking the therapeutic effects of different treatments ( Rouse et al, 2017 ; Pan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%